2010
DOI: 10.1055/s-0030-1255708
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging in the evaluation of villous morphology: a feasibility study assessing a simplified classification and observer agreement

Abstract: Using a simplified classification, we demonstrated the feasibility of using NBI-Z to detect villous atrophy in patients presenting with suspected celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 13 publications
3
29
0
1
Order By: Relevance
“…A few previously published studies have shown similar results [6,7,10]. Table 1 shows the results of these studies along with data from the current study.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…A few previously published studies have shown similar results [6,7,10]. Table 1 shows the results of these studies along with data from the current study.…”
supporting
confidence: 78%
“…The authors have classified the appearance of duodenal villi on magnification NBI into four categories, although this lacked external validation as the authors have mentioned. The appearance of duodenum on NBI endoscopy in patients with normal villi, partially atrophic villi, and completely atrophic villi has been already described in previous studies, and the current study does not provide any additional features for observation [6,7]. However, results from this study are a welcome addition to the data on the usefulness of NBI in duodenal disease.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Indeed, endoscopic imaging has been applied to numerous studies of coeliac disease, which exhibits similar but more extreme changes in intestinal structure to EED, including scalloped duodenal folds, grooves, fissurations and loss of the finger-shaped villi that cover the healthy mucosal surface 23 . The contrast of the villous structure can be enhanced through techniques including water immersion 24 , high-definition (HD) endoscopy 25 , chromoendoscopy 26 , narrow band imaging (NBI) 27 , and other forms of optical or digital chromoendoscopy such as optimal band imaging (OBI) 28 , providing sensitivities and specificities of up to 100% for villous atrophy 25 . FIGURE 2a-d shows the contrast improvement offered by optical chromoendoscopy, revealing clear differences between healthy and unhealthy villous mucosa.…”
Section: Biomarkers For Eedmentioning
confidence: 99%